Interferometric Measurement of TGF-beta Induced Epithelial-Mesenchymal Transition of Tumor Cells - ESMER, GÖKHAN BORA (MDPI, 2020)
A three-dimensional profile reconstruction of live cells in dynamic cell cultures is a challenging problem due to the highly scattering nature of cell mediums. Furthermore, it is an interesting problem since these cultures present the optimal in vitro conditions that most closely resemble the cells' natural conditions. In this paper, we report a holographic method used for imaging during the process of treatment of dynamic cell cultures with transforming growth factor beta (TGF-beta) and the subsequent epithelial-mesenchymal transition (EMT). The imaging of dynamic cell cultures presents many challenges for holographic techniques due to the highly scattering and high speed nature of the environment. Here we report the algorithmic workflow we used for decreasing the imaging noise due to the presence of cell medium and achieving high speed reconstruction rates in real time. We also report the prominent morphological features we extracted from the obtained depth maps throughout the experiment. We conducted experiments on four different cell lines: ONCO-DG1, HCT-116, MDA-MB-231, and HUVEC. We observed the EMT process throughout a 48 h period after treatment with TGF-beta with 6 h intervals for each sample. We show some examples of the reconstructed depth maps of tumor cells during the EMT phase. From these depth maps we extract some morphological parameters and report how they change after the EMT process is completed. The obtained results indicate that the proposed method presents certain advantages from an optical perspective particularly for applications where a dynamical medium is present. These advantages are lower signal-to-noise ratio (SNR) values and a simple setup compared to the setups used in similar studies. Future studies on this application could lead to the development of a model for the EMT process and its effects on cell to cell interactions.
Keywords: digital holographic microscopy; epithelial-mesenchymal transition; tumor cells; DIGITAL HOLOGRAPHIC MICROSCOPY; PHASE-CONTRAST; BLOOD-CELLS; MORPHOLOGY